STATE OF DESIGN EDUCATION IN SINGAPORE – INSIGHTS FROM DESIGN EDUCATION SUMMIT 2018. (May 2020) - Silva, P.; Khan, S.; Blessing, L.
Abstract: This study aims to understand the main issues in design education and discuss solutions. We conducted two workshops on the state of implementation of design in the Singaporean education system at the Design Education Summit, a conference for educators. We found that the main issues were the inclusion of design education within curriculum and change of stakeholder mindsets. Several solutions were discussed, such as ways to introduce design as part of the organization culture. We summarize results into action items and recommendations.